2022
DOI: 10.1007/s00394-022-02848-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations of specific types of fruit and vegetables with perceived stress in adults: the AusDiab study

Abstract: Purpose Higher total fruit and vegetable (FV) intakes have been associated with lower perceived stress. The relationship between specific types of FV and perceived stress remains uncertain. The aims of this cross-sectional study were to explore the relationship between consumption of specific types of FV with perceived stress in a population-based cohort of men and women aged ≥ 25 years from the Australian Diabetes, Obesity and Lifestyle (AusDiab) Study. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…On the other side, some studies have reported that mental health disorders including depression and psychological stress may reduce an individual’s motivation to eat healthy foods and sometime lead to overeating [ 17 ], skipping main meals and replacing them with high calories foods [ 30 ]. Some individuals consume high energy and fatty foods during stressful situations, choosing these more palatable foods as an unconscious or deliberate strategy to change their energy levels and mood [ 52 , 53 ]. Stress affects neuroendocrine function by activating the hypothalamic-pituitary-adrenal (HPA) axis, increasing the secretion of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, some studies have reported that mental health disorders including depression and psychological stress may reduce an individual’s motivation to eat healthy foods and sometime lead to overeating [ 17 ], skipping main meals and replacing them with high calories foods [ 30 ]. Some individuals consume high energy and fatty foods during stressful situations, choosing these more palatable foods as an unconscious or deliberate strategy to change their energy levels and mood [ 52 , 53 ]. Stress affects neuroendocrine function by activating the hypothalamic-pituitary-adrenal (HPA) axis, increasing the secretion of glucocorticoids.…”
Section: Discussionmentioning
confidence: 99%
“…For nutrients, 1 point was assigned when the following criteria were met: (a) free sugar intake at breakfast < 10% total daily energy divided by the number of participants’ daily eating occasions (EO); (b) calcium intake ≥ 20% of the recommended dietary allowance according to participants’ life stage group as indicated by Italian Dietary Reference Intakes [ 28 ]; (c) saturated fat content < 10% total daily energy divided by the number of daily EO; (d) fibre intake > 25 g divided by the number of participants’ EO; and (e) sodium intake < 2000 mg divided by the number of daily EO. For analysis purposes, the BQI was further categorized as low (BQI between 0 and 3), medium (4-6), and high (7-10), as done in prior studies [ 16 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Observational studies of breakfast consumption in association with mental health are also emerging [ 10 12 ]. In addition to the regularity of breakfast intake, specific foods and the quality of breakfast could be crucial for achieving beneficial effects on mental health [ 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Negative thoughts and feelings can generate when an individual experiences great stress in response to stressful life events. Negative thoughts and feelings are known as perceived stress ( 19 ). The cognitive theory of stress states that cognitive evaluation is an important factor in individual responses to stress ( 20 ), and the results of perceived stress are different due to their cognitive evaluation of stress; when an individual is faced with stress, the effectiveness of stress factors depends on the individual’s perceived stress ( 21 ).…”
Section: Introductionmentioning
confidence: 99%